Pertukaran Sosial pada Masyarakat Petambak: Kajian Struktur Sosial Sebuah Desa Kawasan Pertambakan di Sulawesi Selatan - Darmawan Salman; Andin H. Taryoto (Jurnal Agro Ekonomi, 1992)
An important aspect of society in brackish water agro-ecosystem is the nature of social exchange between each party found in the social system. This is very much related to various social status in that society. An analysis on social exchange pattern will be important to identify which linkages that might lead to a more integrative social structure. With a case study of a brackish-based society in South Sulawesi, the analysis is directed toward a "mapping" of social exchange in the society. Spesifically, the study is related to exchange pattern between Ponggawa and Sawi in terms of patron-client approach, tenure system, and its role in establishing social structure of the society. Some important findings of the study are: (1) most interactions between owner and renter, owner and share holder, owner and sawi, renter and share holder, renter and sawi, and share holder and sawi, are institutionalized through ponggawa-sawi relationship, share holding, and renting; (2) ponggawa-sawi relationship in terms of patron-client linkages dominated by imited exchanges tends to create segmental social structure, while share holding and renting that are dominated by general exchange pattern tend to create a more integrative social structure; (3) imbalance exchanged to both parties; ponggawa is in exploitative side, while sawi is in sub-ordinated one; and (4) strategy for society development in the study site should then consider those social exchange patterns as one most important factors to be considered. This is especially central for the implementation of cooperative and credit program directed toward parties enggaged in those exchange patterns.